The Value Inheritance of Family System in Islamic Tradition: Birr-ul-Walidayn - Ade Hidayat; Akhsan Sukroni (Universiti Sains Islam Malaysia, 2024)
Birr-ul-walidayn (filial piety) has a great importance in Islamic parenting besides educating and nurturing children. The emphasizing of its significance is laid on God’s order of its obligation that always associated with the obligation of Tawhid (monotheistic as a primary beliefs in Islam). Islamic teaching has arranged an integrated rule then create Islamic tradition where consist birr-ul-walidayn inside by exampling of some the best and historical parents noted by Quran included some prophets that contained some values of harmonious relationship between parent and children, quality education and guidance for children and also filial piety. On the contrary, flaws or unfinished task of family and parents on the process will make some hindrances or problems in the family and also in the society in many aspect. In short, the role of family has a great deal in value inheritance as religion claimed in rules and prophetic true stories.